DKN-01 and tislelizumab as second-line therapy in DKK1-high gastroesophageal adenocarcinoma: DisTinGuish trial part B - Keun-Wook Lee; Devalingam Mahalingam; Byoung Yong Shim; In-Ho Kim; Do-Youn Oh; Hope Uronis; Sun Jin Sym; Mohamad Sonbol; Khaldoun Almhanna; Mohamedtaki A. Tejani; Beodeul Kang; Michael H. Kagey; et al. (Nature Communications)
Abstract Biomarker-enriched, chemotherapy-free treatments for patients with advanced gastric and gastroesophageal junction cancer have not been widely explored. In this multicenter, phase 2 trial (NCT04363801), we evaluated the efficacy and safety of second-line doublet immunotherapy, combining DKN-01, an immunomodulating antibody targeting Dickkopf-related protein 1 (DKK1), with the anti-programmed cell death-1 (PD1) antibody, tislelizumab in patients with advanced gastric/gastroesophageal junction cancer and elevated tumor DKK1 expression, a putative predictive biomarker for DKN-01. Here we report part B (second line cohort) of the larger DisTinGuish trial. The primary endpoint was safety and tolerability, with secondary endpoints including objective response rate (ORR), overall survival (OS), progression free survival (PFS), and disease control rate (DCR). The trial met the prespecified primary endpoint. In the safety population (n = 52), 21 (40.4%) patients reported at least 1 DKN-01-related adverse event, most of which were low-grade, with fatigue (15.4%) and nausea (9.6%) being most common. The ORR was 21.7% in the overall population (n = 46) and 31.8% in the programmed death-ligand 1 (PD-L1) ≥ 5% population. The median OS was 8.2 months, median PFS 1.4 months, and DCR rate 34.8% in the overall population. Although exploratory, the results of this trial compare favorably against second-line benchmarks of Keynote-061 and RAINBOW and support the safety and tolerability of DKN-01 combined with tislelizumab.